Preterm Caesarean Delivery in a Parturient with Candida parapsilosis Endocarditis. (29th June 2015) - Fu, Jason; Retherford, Lance M.; Flynn, Brigid
Abstract : We present the first documented case of Candida parapsilosis infective endocarditis in a pregnant patient. While the incidence of infective endocarditis during pregnancy is rare, the incidence of C. parapsilosis endocarditis is even rarer. The numerous specific risks and decision making processes regarding this case are presented.